A Relook into Visceral Slide Test as a Preoperative Screening Modality to Detect Abdominal Wall Adhesions: A Prospective Observational Cohort Study - Jain, Himanshi; Shivananda, Roopa P.; Rao, Shubha; Hegde, Nivedita; Paladugu, Sangamithra; Vasudeva, Akhila (Current Women's Health Reviews, 2022)
Background: Ultrasound has become an invaluable tool in our daily practice. Its role in screening for adhesions has been tested since the 1990s. Objective: This study aims to determine the role of the visceral slide test as a screening method to predict abdominal wall adhesions in women undergoing gynecological surgery. Methods: We conducted a prospective observational cohort study from August 2017 to July 2019 in women undergoing elective abdominopelvic surgery for a gynecological indication. Preoperatively, a visceral slide test was performed in 5 specified zones on the abdomen and the test results were clinically correlated with the presence, severity, and extent of adhesions intra-operatively. Results: Results were reported as mean, standard deviation, range of values or number and percent. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy (including 95% confidence interval for all) of visceral slide test were calculated to determine intra- abdominal adhesions . We also found a correlation between the number of negative slide tests and PAI scores using Spearman’s correlation test. Of the 339 women who completed the study, 41.2% had a previous history of abdominopelvic surgery. In this study, the visceral slide test was found to have a sensitivity of 70.87% (95%CI 62.15-78.59), specificity of 86.32% (95% CI 80.95-90.64), Positive Predictive Value (PPV) of 75.63% (95% CI 68.49-81.59), negative predictive value (NPV) of 83.18%(95% CI 78.95-86.70) and diagnostic accuracy of 80.53%(95% CI 75.91-84.61)with p-value less than 0.001. The number of negative slide tests positively correlated with the Peritoneal Adhesion Index score (r = 0.662, p < 0.001) and also with increasing operative time and intraoperative blood loss. Accuracy and positive predictive value of the test were significantly higher in patients with a history of abdominal surgeries, endometriosis and PID. Conclusion: Visceral slide test is an easy, rapid, non-invasive and reliable screening test to predict abdominal adhesions in women undergoing gynecological surgery. The presence of risk factors for adhesions increases the accuracy of the test.s
Keywords: Transabdominal ultrasound